Wątki kryminalne w wybranych powieściach historycznych dla młodzieży Walerego Przyborowskiego = Elements of crime fiction in Walery Przyborowski's historical novels for teenagers - Kaczmar, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Although Walery Przyborowski has been forgotten as a writer today, in the past his novels playedan important role in the patriotic formation of young Polish boys. Although Przyborowski wrotehistorical novels, he introduced in them a number of elements characteristic of criminal fiction. Themain aim of this article is to discuss these elements as used in his selected novels for children andteenagers; it is also to indicate their contribution to the genre which Przyborowski took up next, thatis, the novel of manners with a crime story in the background.
Keywords: Przyborowski, Walery (polski historyk, pisarz; 1845-1913); powieść polska - 19 w.; literatura dla dzieci i młodzieży; literatura polska - 19 w. - tematyka